2018
DOI: 10.1136/heartasia-2018-011062
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of 30-day mortality in patients with ventricular septal rupture complicating acute myocardial infarction

Abstract: In this retrospective cohort of patients with AMI, the occurrence of VSR was not rare and carried a considerable risk of 30-day mortality. Advanced age, previous cerebrovascular accident and surgical repair influenced the risk for 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
1
10
1
Order By: Relevance
“…This is comparatively lower than the 1–3% VSR rate reported in studies conducted in the pre-reperfusion era [ 17 ]. In a study conducted in India, the rate of VSR was comparable to our findings (0.7%) [ 18 ]. However, the incidence of VSR in the GUSTO-1(Global Utilization of Streptokinase and TPA for Occluded Coronary Arteries) trial was slightly lower (0.2–0.4%) as compared to our findings [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is comparatively lower than the 1–3% VSR rate reported in studies conducted in the pre-reperfusion era [ 17 ]. In a study conducted in India, the rate of VSR was comparable to our findings (0.7%) [ 18 ]. However, the incidence of VSR in the GUSTO-1(Global Utilization of Streptokinase and TPA for Occluded Coronary Arteries) trial was slightly lower (0.2–0.4%) as compared to our findings [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our in-hospital VSR related mortality rate was 65.7%. However, a study conducted in similar resource-limited settings on post-MI VSR patients suggested a higher rate (80.4%) of in-hospital mortality [ 18 ]. In contrast, findings from developed countries exhibited comparatively lower rates of early VSR related mortality ranging from 35%-54% [ 17 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular septal rupture (VSR) is a serious complication after an acute myocardial infarction (MI). The incidence of VSR was 1% to 3% in the era before accessible reperfusion practices [ 1 ]. However, the incidence has declined in recent years to around 0.3% following the emergence of thrombolysis and primary percutaneous coronary intervention (PPCI) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular septal defects complicating STEMIs are associated with high mortality, prevailing at 50% even after surgical repair [3]. Fatality is significantly higher in patients of advanced age [4].…”
Section: Discussionmentioning
confidence: 99%